Farmers’ Strategies for Adapting to and Mitigating Climate Variability and Change through Agroforestry in Ethiopia and Kenya - Bishaw, Badege; Neufeldt, Henry; Mowo, Jeremias; Abdelkadir, Abdu; Muriuki, Jonathan; Dalle, Gemedo; Tewodros, Assefa; Guillozet, Kathleen; Kassa, Habtemariam; Dawson, Ian K.; Luedeling, Eike; Mbow, Cheikh (2013)
I would like to thank the World Agroforestry Center (ICRAF), Nairobi, Kenya, for providing funds through the USAID Linkage Project to initiate collaborative research, student and faculty exchange, and the exchange of scientific information between Oregon State University and the World Agroforestry Center. Also, Oregon State University, the Wondo Genet College of Forestry and Natural Resources, Hawassa University, Hawassa, Ethiopia, the Institute of Biodiversity Conservation (IBC), Addis Ababa, Ethiopia, and the Center for International Forestry Research (CIFOR), Addis Ababa, Ethiopia.
openalex: W1535089209 mag: 1535089209
Keywords: openalex:import